Urgency of Instructional Training Based on Muhammadiyah Values: A Site Study of ABA Kindergarten Teachers - Mufnaetty, Mufnaetty; Masrukhi, Masrukhi; Prihatin, Titi (The Journal of Educational Development, 2018)
Kindergarten teachers are one of the spearheads of education. Therefore, their technical skills need to be improved, one of which is through training. The training offered to the teachers of Aisyiyah Bustanul Athfal (ABA) Kindergarten is a training that is based on Muhammadiyah values (NNK). NNK is a value system built on the four pillars of Islamic worldly teachings (aqidah, akhlak, ibadah, and muamalah) which are the results of tarjih and have been cultivated so as to have the power to be referred to in managing and activating the organization and its business of charity as a guide for the citizens of Muhammadiyah. This study aimed to answer the questions: 1) How is the instructional training based on the Muhammadiyah values for the ABA Kindergarten teachers? 2) How is the management of the NKK-based instructional training for the ABA Kindergarten teachers? 3) How is the urgency of the ABA Kindergarten teachers on the NKK-based instructional training? This research utilized a qualitative design. The key informants: DIDASMEN and IGABA Council Managers; the additional informants: ABA Kindergarten teachers and the head of the ABA Kindergarten. The data were validated using the credibility and research tests that are focused more on triangulation and checking. The results show that 1) ABA Kindergarten teachers have not been able to implement NNK as a basis in learning; 2) four management functions have not been fully implemented in the management model for the ABA Kindergarten teachers; 3) the NKK-based instructional training is urgent to be given and mastered by the ABA Kindergarten teachers.